COMPOST AND FOLIAR IRON ENHANCED FRUIT PRODUCTION AND QUALITY OF GREWIATENAX (F ORSK.) FIORI. UNDER STRESSED ENVIRONMENT - A. A. Elfeel; R. A. Abohassan (Journal of Animal and Plant Sciences, 2019)
Grewia tenax is a multi-values tree well adapted to high salinity and prolonged drought spells. However, the species still remains underutilized in the natural fields. In this study field performance and production of Grewia was investigated in arid saline land using a combination of compost addition and foliar spraying of EDDHA iron chelate during the years 2016- 2017. The combined effects of compost with chelated iron resulted in higher Canopy Cover (CC) and Relative Monthly Branch Increment (RMBI). The increase in CC and RMBI accompanied with better Fruit Set Rate (FSR) and fruit production. In turn, trends in CC over time showed seasonal pattern reflecting adaptation to changes in atmospheric conditions. Fruit individual sugars (Fructose, Glucose, Sucrose and Maltose), macro elements (K, Ca and Mg) and minor elements (Fe, Cu and Zn) contents were positively affected by fertilization rate, except Na that showed reverse trend. Whereas fructose, glucose and K contents were the higher. In most of the studied traits compost + iron obtained greater values, even at lower compost doses. The results revealed that under arid conditions compost and foliar iron increased the green canopy that enhanced growth performance and fruit quantity and quality. This high light the potential prospects of domesticating this species in arid environments.
Keywords: Compost; foliar iron; canopy cover; fruit; minerals; sugars